Numerical solution of nonlinear elliptic equation with nonlocal condition - Čiupaila, Regimantas; Sapagovas, Mifodijus; Štikonienė, Olga (Nonlinear Analysis: Modelling and Control, 2013)
Two iterative methods are considered for the system of difference equations approximating two-dimensional nonlinear elliptic equation with the nonlocal integral condition. Motivation and possible applications of the problem present in the paper coincide with the small volume problems in hydrodynamics. The differential problem considered in the article is some generalization of the boundary value problem for minimal surface equation.
Keywords: minimal surface equation; nonlocal boundary condition; finite-difference method; iterative method